Wille and Willkür: an analysis and an interpretation in the philosophy of Kant - de Souza, Draiton Gonzaga; Bresolin, Keberson (Veritas (Porto Alegre), 2019)
Kant, along his thought, deepened and clarified the concepts of Wille and Willkür. Both concepts are fundamental to understanding the possibility of freedom, be it internal or external. The rational philosopher uses the concepts of Wille and Willkür from the Kritik der reinen Vernunft, but it will only be in the late work of the Metaphysik der Sitten (1798) that concepts will have semantic precision within the system of the metaphysics of freedom. As a result, we will go through the critical Kantian works from the Kritik der reinen Vernunft to the Metaphysik der Sitten to verify the “different” formulations of the Wille and Willkür concepts and, finally, to consider the one that seems most plausible in line with a systematic reading of Kantian thought.